A Risk-averse Two-Stage Stochastic Optimization Model for Water Resources Allocation under Uncertainty - Xu, Ye; Li, Sha; Liu, Feng; Qian, Jinping; Cai, Yanpeng; Cheng, Guanhui (Journal of Environmental Accounting and Management, 2026)
The water resource shortage has caused intense contradictions among various water users; moreover, unfair and irrational water allocation may result in the economic loss, even the social instability. A risk-averse twostage stochastic programming model (RATSP) are developed for tackling this issue. The significant contribution made by the RATSP model is that it concerns the importance of the financial risk under each scenario, where the risk is expressed as the probability of occurrence in that benefit generated under each scenario is lower than predefined target profit. It can avoid possible suboptimal solutions caused by only considering the maximization of the expected value for all scenarios as an objective function. Moreover, the risk measure is incorporated into the objective function, leading a variety of solutions under various weight coefficients and target levels, which is suitable in analyzing the trade-off between the system economy and reliability. A case of water resources management system is used to reflect the applicability and feasibility of this model. The obtained results demonstrate that the RATSP model can help decision makers gain in-depth insights into potential system risk, analyze the trade-off between system economy and stability, generate the stable water allocation schemes, and avoid the contradictions among users.